The Integration Substitute: The Role of Controls in Managing Human Asset Specificity - Sridharan,V.G.; Akroyd,Chris (Accounting and Finance, 2011)
As the integration solution to the problem of specific assets cannot be replicated on human asset specificity because slavery is illegal, economic theory states that control systems substitute for integration through a balanced structure to help align diverse interests. To understand the intricate design features of the balance, we examine a case-study firm. For low human asset specificity, the restriction and segregation of usable decision rights link with standards. However, incentives are traced to individuals only to the extent task deviations do not create relevant future costs that are difficult to be self-corrected. For high specificity, incentives are related to outputs rather than outcomes, because outcome variations reduce the attractiveness of maintaining the balance. Subjective assessment is used as an efficient alternate ‘balancing’ solution and decision control is shared when available subjective data are inadequate.
Keywords: Accounting